Quantitative assessment of the retinal microvasculature using optical coherence tomography angiography - Chu, Zhongdi; Lin, Jason; Gao, Chen; Xin, Chen; Zhang, Qinqin; Chen, Chieh-Li; Roisman, Luis; Gregori, Giovanni; Rosenfeld, Philip J; Wang, Ruikang K (Journal of biomedical optics, 2016)
Optical coherence tomography angiography (OCTA) is clinically useful for the qualitative assessment of the macular microvasculature. However, there is a need for comprehensive quantitative tools to help objectively analyze the OCT angiograms. Few studies have reported the use of a single quantitative index to describe vessel density in OCT angiograms. In this study, we introduce a five-index quantitative analysis of OCT angiograms in an attempt to detect and assess vascular abnormalities from multiple perspectives. The indices include vessel area density, vessel skeleton density, vessel diameter index, vessel perimeter index, and vessel complexity index. We show the usefulness of the proposed indices with five illustrative cases. Repeatability is tested on both a healthy case and a stable diseased case, giving interclass coefficients smaller than 0.031. The results demonstrate that our proposed quantitative analysis may be useful as a complement to conventional OCTA for the diagnosis of disease and monitoring of treatment.